VD_FINDINFO HC / 2009 / 413 vom 24. November 2009 - VD Tribunal cantonal (2009)
MESURE DE CONTRAINTEDROIT DES ÉTRANGERS, DÉTENTION AUX FINS D'EXPULSION | 76 al. 1 let. b ch. 1 LEtr, 30 LVLEtr, 31 LVLEtr